2014
DOI: 10.1007/s00167-014-2942-4
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cross-cultural adaptation and validation of the French version of the Anterior Cruciate Ligament-Return to Sport after Injury (ACL-RSI) scale

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
97
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 24 publications
(29 reference statements)
34
97
3
Order By: Relevance
“…There was no significant difference in the other functional knee scores or in patient satisfaction (Table 5). Table 2 Surgical data for ACL reconstruction (1) Hamstring tendon, (2) Bone-patellar tendon-bone, (3) Combined fasciae latae for intra-and extraarticular anterior cruciate ligament reconstruction, (4) Tensor fasciae latae tendon…”
Section: Functional Knee Scores At 1 Year Of Follow-up and Patient Samentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in the other functional knee scores or in patient satisfaction (Table 5). Table 2 Surgical data for ACL reconstruction (1) Hamstring tendon, (2) Bone-patellar tendon-bone, (3) Combined fasciae latae for intra-and extraarticular anterior cruciate ligament reconstruction, (4) Tensor fasciae latae tendon…”
Section: Functional Knee Scores At 1 Year Of Follow-up and Patient Samentioning
confidence: 99%
“…Type of graft HS (1) 977 (82.5%) 352 (71.8%) < 10 −4 BPTB (2) 115 (9.7%) 38 (7.8%) CFL (3) 92 (7.8%) 100 (20.4%) Extraarticular tenodesis (FLT (4) Factors favouring the return to the preinjury sport Univariate analysis showed that compared to patients who did not return to their preinjury sport at the 1-year follow-up, patients who did return to their preinjury sport were significantly younger and lighter, were professional or competitive athletes without a prior history of knee surgery, had better preoperative functional and psychological scores (subjective IKDC, KOOS daily life, sports and quality of life, Lysholm and ACL-RSI), belonged to the "with vancomycin" group, underwent associated extraarticular reconstruction, presented with fewer medial meniscal lesions, and did not present with complications during the first year after surgery, in particular septic arthritis ( Table 6). The final multivariate analysis included the study group (1 or 2), age under 25, male gender, competitive or professional sport, a history of knee surgery, preoperative scores (subjective IKDC ≥ 65, KOOS daily life ≥ 85, KOOS sport ≥ 70, KOOS quality of life ≥ 40, ACL-RSI ≥ 55), the association of extraarticular reconstruction, the presence of a medial meniscal tear, the development of a severe complication during the first year (including an infection and a homolateral retear).…”
Section: Functional Knee Scores At 1 Year Of Follow-up and Patient Samentioning
confidence: 99%
“…The IKDC, Marx, Lysholm, and Tegner scales are all validated outcome measures that have long been used in the evaluation of knee injuries and the global assessment of recovery following clinical interventions [2,12,16,18,19,26,30]. Descriptions of each outcome measure are included in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The ACL-RSI has been shown to discriminate between athletes who return and athletes who do not return to sport after reconstruction surgery. The scale was recently validated in Swedish and French (Bohu, Klouche, Lefevre, Webster, & Herman, 2015;Kvist et al, 2013). In the Netherlands, there is need for a questionnaire that measures the psychological impact of returning to sport after ACL injury or reconstruction.…”
Section: Introductionmentioning
confidence: 99%